Peningkatan Kesadaran Masyarakat tentang Pentingnya Perilaku Menjaga Kebersihan Lingkungan - Ahmad Jainudin; Arif Rahman Hakim; Aisyah Rizki Nuralvani; Anggi Komalasari; Kessia Kristina Hutabarat; Normala; Putri Handayani; Rafi Ardani (Prodi Sosiologi FISIP ULM, 2023)
Throwing rubbish carelessly into the river is one of the problems found by the community service team in Tanipah Village, Mandastana District, Barito Kuala Regency. This indicates a lack of public awareness of the environment in which they live. With that, the issues raised in this service program are cleanliness and public awareness of environmental sustainability. This is the background for the service team to carry out education to increase understanding about the behavior of maintaining environmental cleanliness. The aim of this program is to build a cleaner and neater village, to establish good interaction between the community and the environment. The implementation method uses intervention logic based on the empowerment approach, namely enabling, empowering, and protecting. Service activities are carried out live in where the service team stays overnight and is intensely involved with the community for 37 days, from 16 July-21 August 2023. The service team carries out 3 service programs, namely: 1) Nature School; 2) Balingai (mutual cooperation cleaning up rubbish); and, 3) Dividing Plant Seeds. The achievement of this activity is the community's willingness to maintain cleanliness and environmental sustainability. The results of this service program provide awareness of protecting the environment as shown by the physical changes in Tanipah Village, namely that the environment is starting to be clean and tidy. Where previously there was a lot of rubbish strewn about and the land was starting to become barren. In the process of implementing the service program, the active role of the community and supporting institutions ensures that activities are carried out well.